THE NEW GENERATION OF HIGH QUALITY ESL/EFL TEACHERS: A PROPOSAL FOR INTERDISCIPLINARY TEACHER EDUCATION - Syahril, Iwan (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2019)
In this paper I argue that ESL/EFL teacher education programs should be the leading agents of change in transforming a nation. With its emphasis on English mastery, an ESL/EFL teacher education program generally produce teachers with sufficient English to comprehend development/global issues such as climate change, poverty, or inequality. The emphasis on the mastery of English as the international language will make pre-service teachers relatively better able to understand and produce multimodal English texts around those development/global issues compared to pre-service teachers from other subjects. Building on the earlier work such as in Content and Language Integrated Learning (CLIL) and content area literacy, ESL/EFL teacher education can realize this vision with an innovative idea: an interdisciplinary teacher education program. In this program, I envision that an ESL/EFL pre-service teacher education program collaborates with other subject area teacher education programs (e.g., social studies, science) working on an overreaching theme, such as sustainable development, or others. Pre-service teachers learn the learning outcomes of subject areas not in isolation but in an integrated manner. They learn inter-(disciplinary) content knowledge and pedagogical content knowledge around global issues and universal values. Arguably, this kind of program will create teachers who can think critically, systemically and creatively, using a multi-perspective approach that recognizes the different dimensions, perspectives and angles of issues. At the same time, this kind of program can produce teachers with key non-cognitive skills such as empathy, communication skills and aptitudes for interacting and collaborating with people of different backgrounds, origins, cultures and perspectives. Indeed, this is a proposal for a new generation of (language) teachers, the ones who can teach 21st century skills (e.g., critical thinking, communication, collaboration, creativity) with innovative forms of teaching (e.g., project-based learning, problem-based learning, inquiry-based learning, theme-based learning) around authentic problems with a multi-perspective approach. Indeed, for a developing nation, such as Indonesia, having quality teachers who can think and teach in an interdisciplinary manner can be very strategic not only in improving and transforming its education but also for accelerating its social and economic development.DOI: doi.org/10.24071/llt.2019.220104